APPLICATION OF AUTOMATIC WATERING SYSTEM FOR SMART AGRICULTURE AT PEKARANGAN PANGAN LESTARI SENGKOLO MAKMUR - Yuli Prasetyo; Budi Triyono; Dimas Nur Prakoso; Hanifah Nur Kumala Ningrum; Budi Artono; Agus Choirul Arifin; Ade Reza Febri (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Food security is an important aspect in maintaining people's welfare. However, the main challenge in managing pekarangan as a food source is the efficient management of water for watering plants. Sengkolo Makmur has a yard that is used for food security in the Josenan area of Madiun City. So far, watering is done manually using human power. This watering is also not scheduled so that if the owner of the yard is busy then watering cannot be done. The use of an automatic watering system in the yard has become an innovative solution in increasing the efficiency of water management and plant care. The research method used includes discussions with the management, prototype design, and field trials. This activity describes the steps for designing and developing an automatic watering system involving temperature sensors, water pumps, and time controllers. The watering system is also equipped with a time controller to adjust the watering time according to the needs of plants at various times and seasons. This activity can be a guide for Sengkolo Makmur sustainable food garden managers in applying smart technology for water conservation and developing a greener environment.